Analysis of the Implementation of the Joint Analysis between the Directorate General of Customs and Excisewith the Directorate General Of Taxes In Increasing State Revenue In The Prime Customs And Excise Office Type A Tanjung Priok - Dian Wahyudi; Novianita Rulandari; Ratih Kumala; Pebriana Arimbhi; Eka Rofiyanti (Budapest International Research and Critics University, 2021)
Collecting revenue targets has always been a challenge due to international taxes and relies heavily on the state of the world economy. Many factors that cause the non-achievement of the revenue target, such as the growth of Exports and Imports of Indonesia has slowed or grown negatively so that it is necessary to carry out joint analysis between the Directorate General of Customs and Excise together with the Directorate General of Taxation as an institution that has the task of collecting state revenues. The purpose of this research is to know the implementation of joint analysis between the Directorate General of Customs and Excise together with the Directorate General of Taxation. The research method used is qualitative descriptive method with interview research techniques, observation, and using secondary data. The results of the author's research are one indicator that has not been carried out to the maximum, namely the characteristics of the implementing organization, where there needs to be actors in the implementation of the policy and the division of duties and authorities. This is evidenced by the absence of standardized SOPs in the implementation of joint analysis that causes overlap and mutual waiting in starting an action that needs to be done. This is one of the things that needs to be a concern if the joint analysis wants to continue to be carried out continuously.